MODEL DEVELOPMENT OF COOPETITION RELATIONSHIP TOWARDS LOGISTICS SERVICE QUALITY BY CONSIDERING THE COMPANY CHARACTERISTICS OF COURIER, EXPRESS, AND PARCEL SERVICES - Devi Santika, Tiara
Amid the development of eCommerce, the role of the logistics sector cannot be ignored. Indonesia has the fastest-growing logistics sector in Southeast Asia. Unfortunately, this performance is not supported by the sector quality as indicated by the low LPI score and the competitiveness of indonesian logistics. As a solution, innovation that has been proven to improve the quality of various industries continues to be encouraged. Focusing on logistics services categories most relevant to eCommerce, namely courier, express, and parcel services, there is a dominance of key players in the market, indicating uneven capabilities among them. By elaborating on the relational view of resource-based theory (RBT), coopetition is considered necessary. Literature studies show limited research on the relationship between coopetition and LPS as the primary performance of logistics services. The research involves 12 research constructs and data from 106 employees of conventional companies and 95 employees of non-conventional companies. The model development is carried out using Partial Least Squares Structural Equation Modeling (PLS-SEM). The research results show significant differences between conventional and non-conventional companies data, indicating that data processing needs to be done separately. Furthermore, significant relationships are found between alliance management and coopetition, coopetition and innovation, and innovation and Logistics Service Quality (LSQ). Data processing for conventional companies indicates the role of trust as a moderator between coopetition and LSQ, and LSQ components consist of timeliness, personnel contact quality, and operational information quality. On the other hand, data processing for non-conventional companies indicates the role of variable as a moderator between coopetition and LSQ, and LSQ components consist of timeliness and operational information quality.